Assessment of Premutation in Myotonic Dystrophy Type 1 Affected Family Members by TP-PCR and Genetic Counseling - Ashok Kumar; Sarita Agarwal; Sunil Pradhan (Case Reports in Medicine)
Myotonic dystrophy type 1 (DM1) is caused by the expansion of an unstable CTG repeat located in the 3′-UTR of (DMPK) the DM protein kinase gene. Patients with DM1 have expansions of greater than 50 repeats and up to many thousands. In the present study we aimed to evaluate the utility of TP-PCR in diagnostics as well as the assessment of premutation carriers in proband families. Twenty-seven DM1 cases were enrolled (from twenty-six families) and the 13 families of these cases came forward for family screening. The patient group constitute 22 males and 5 females and the average age of onset was 32.8 years (range 17 to 52). All clinically diagnosed DM1 cases and their family members DNA samples were analyzed by TP-PCR. All the cases were found to be positive for the CTG repeat expansion. Among those five families, four had at least an asymptomatic carrier. In the remaining one family other than the proband none was found to be neither affected nor asymptomatic. We reconfirmed the utility of PCR based screening for DM1 as being reliable and rapid molecular test and it should be used as an initial screening test for all patients with DM and their family members for initial screening purpose.